Competencias ciudadanas en estudiantes de municipios escolares de pachacamac, desde su experiencia en presupuestos participativos - Alzamora de los Godos Urcia, Luis Alex; Abad Fretel, Julio Anastacio; Calderón Saldaña, Jully Pahola; Valladolid Marcos, Fiorella Sthefany; Pineda Medina, Javier Alejandro; La Torre Palomino, Jorge Luis; Oriundo Verástegui, Juan Gerardo (LACCEI, 2024)
This study aims to identify the civic competencies developed by students from the school municipalities of the Pachacamac District through their participation in participatory budgeting. Employing a qualitative exploratory design with a descriptive approach, the research includes an assessment questionnaire for 114 high school students who were not part of the school municipalities in 2018, along with 10 semi-structured interviews and three focus groups with students who were involved. Students described their experiences in participatory budgeting as highly rewarding, especially when their projects were selected as winners among many educational institutions. These successes brought financial capital to their schools, addressing urgent needs in infrastructure and educational equipment. However, they also faced challenges, such as delays in project execution caused by adults, despite available funding. Although students do not fully understand these issues, they are eager to continue participating in their municipality's participatory budgets, believing it essential for learning democratic and participatory practices. Participation in school municipalities has equipped students with citizenship skills that will benefit them as future responsible citizens. Their involvement in the municipal participatory budget process promotes knowledge that enables them to make better decisions as citizens and encourages democratic engagement in community development, ultimately enhancing their quality of life.